Advances in Diagnosis of Skin and Superficial Tissue Disorders—“Old and Emerging” Diagnostic Tools - Costantino Ricci (Diagnostics)
Skin and superficial tissue disorders (SSTDs) are some of the most common diseases affecting humans [...]